The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1971
DOI: 10.1104/pp.47.5.696
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Biosynthesis in Fruit Tissues

Abstract: Tracer studies with avocado tissues indicate that methionine is converted to ethylene at stages of the climacteric rise and the climacteric peak, but not at the preclimacteric stage. The results suggest that the control of ethylene biosynthesis is at a step after methionine is synthesized. The endogenous content of methionine was found to be so low that methionine must be actively turned over for ethylene biosynthesis during the stages when the rate of ethylene production is high. Oxygen was found to be essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…He suggested that under anaerobic conditions the proposed intermediate accumulated and that a surge of ethylene production occurred upon exposure to 02. Such a surge has been reported for apples (3,10) and pears (14). The rate of ethylene production increased in plants which had been partially frozen (13,28,32), cold-stressed at 5 C (11,26,30), or heat-stressed at 40 C (15).…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…He suggested that under anaerobic conditions the proposed intermediate accumulated and that a surge of ethylene production occurred upon exposure to 02. Such a surge has been reported for apples (3,10) and pears (14). The rate of ethylene production increased in plants which had been partially frozen (13,28,32), cold-stressed at 5 C (11,26,30), or heat-stressed at 40 C (15).…”
mentioning
confidence: 56%
“…The magnitude of the response varied slightly from experiment to experiment, but the time sequence was constant for tissue excised from a given region of the pea seedling. In this study we examined the 02 and temperature dependency of woundinduced ethylene synthesis by etiolated 'Alaska' pea stem sections.Vegetative, ripening, and senescent tissue require 02 for ethylene synthesis (1,3, 6,13,21,29 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, albedo has been used for studying the mode of ethylene production in the Satsuma mandarin. Methionine has been shown to be a precursor of ethylene in plants (2,7). In the present experiments L-[I4C]methionine was used to test the efficiency of methionine as a possible precursor of ethylene in the albedo tissue.…”
mentioning
confidence: 99%
“…This was verified in banana (5), tomato (9), and avocado (3) fruits. Baur et al (3) demonstrated that the levels of applied, labeled methionine in avocado fruits dropped 60% during the respiratory climacteric rise. Similar results were reported by Yu et al (18) with endogenous free methionine in tomato fruits.…”
mentioning
confidence: 99%